Remittances and Output Growth Volatility in Developing Countries: Does Financial Development Dampen or Magnify the Effects. (2019)
The paper empirically investigated the relationship between remittance flows and output growth volatility for an extensive sample predominated by emerging and developing countries. Following this broad treatment, it goes further to estimate the extent to which the degree of financial development (FD) impacts on the remittances– growth volatility nexus. This novelty distinguishes the work from previous studies. Using the system-generalized method of moments estimator, which corrects for endogenity and omitted variable concerns, on data spanning the period 1996–2012 for a total of 71 countries some interesting findings ensued. One, both remittances and FD had growth volatility dampening effects. Two, the interaction between proxies for FD and remittances produced mixed results. Three, when volatility of FD is accounted for, the interactive term had mixed results. For instance, banking sector credit produces positive and insignificant coefficients, while private sector produced significant and negative coefficients. Summarily putting these results in other words, the countercyclicality of remittances was established, while the complementary dampening effect of financial development is dependent upon its measure. On the basis of the foregoing, a few related policy lessons are documented to conclude the paper.